2010
DOI: 10.1007/s00421-010-1426-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treadmill exercise training on liver fat accumulation and estrogen receptor alpha expression in intact and ovariectomized rats with or without estrogen replacement treatment

Abstract: To explore the mechanism(s) of exercise training on ovariectomized (OVX)-induced liver lipid disorder, we observed effects of treadmill training on liver fat accumulation and ER alpha expression in intact and ovariectomized rats. Sixty female rats were randomly assigned to six groups: Sham sedentary (S-S), Sham exercised (S-EX), ovariectomized sedentary (O-S), ovariectomized exercised (O-EX), ovariectomized injected subcutaneously with 17beta-estradiol (E(2)) (O-E(2)), and ovariectomized treated with E(2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 30 publications
2
38
1
5
Order By: Relevance
“…Some studies have demonstrated that exercise training can increase the level of ERs, which may account for the estrogenic-like effects of exercise. 29) The present study showed that the level of ERα in myocardium was significantly downregulated in OVX rats, and exercise training could restore the ERα expression in OVX rats. This suggests that exercise-induced CSE expression might be due to the upregulation of ERα.…”
Section: Discussionsupporting
confidence: 48%
“…Some studies have demonstrated that exercise training can increase the level of ERs, which may account for the estrogenic-like effects of exercise. 29) The present study showed that the level of ERα in myocardium was significantly downregulated in OVX rats, and exercise training could restore the ERα expression in OVX rats. This suggests that exercise-induced CSE expression might be due to the upregulation of ERα.…”
Section: Discussionsupporting
confidence: 48%
“…Immunohistochemistry was performed as previously reported (Hao et al 2010), but minor reversion was done. In brief, tissue sections were deparaffinized, rehydrated, and rinsed with PBS.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Western blot was also performed as previously reported (Hao et al 2010). In brief, about 20 lg proteins from each sample were loaded onto 10% SDS-PAGE and transferred onto a PVDF membrane (MILLPORE).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Physical training applied to rats can provide information concerning the metabolic alterations promoted by diseases, diet, surgeries and drugs in relation to homeostasis preservation de Souza et al 2003;Soares de Alencar Mota et al 2008;Gomes et al 2009;Leme et al 2009;Bocalini et al 2010;Botezelli et al 2010;Cambri et al 2010;Hao et al 2010). However, a reduced number of researches are concerned to study different protocols of training for these animals to correlate the intensity, duration, and frequency with the performance Carvalho et al 2005;Laursen et al 2007;Caperuto et al 2009).…”
Section: Introductionmentioning
confidence: 97%